Automated extraction of agronomic parameters in orchard plots from high-resolution imagery - Recio J.; Hermosilla T.; Ruiz L.A. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
The availability of high spatial resolution images obtained from aerial and satellite sensors together with the development of new image analysis methods are providing an important impulse to precision agriculture techniques and applications. We describe an automated methodology for the extraction of agronomic parameters from tree orchard plots based on the use of high-resolution remotely sensed imagery, which can be further used to increase the efficiency of irrigation and agricultural plot management in the SUDOE area. These methods are based on parcel-based image analysis, and a variety of parameters are obtained including tree detection, location and counting, planting patterns, tree crown, vegetation cover and others. Since common data and image processing techniques are used, they can be easily implemented in production processes and cover large agricultural areas. The methods are tested on citrus orchard plots located in Valencia (Spain), showing a good performance in particular for adult trees. In addition to the particular use of the ground cover for the estimation of water requirement, these parameters can also be used as support tools for agricultural inventories or database updating, allowing for the reduction of field work and manual interpretation tasks.